2022
DOI: 10.5430/jct.v11n1p59
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Critical Thinking Technologies on Improvement of Students Performance During Self-Study

Abstract: Applicability of the article is preconditioned by the requirements of information-oriented society that dictate modern youth the necessity of work with information ability, to see, to envisage and to correct logic errors. In modern world it is important to conduct reflection of own activity that maintain the necessity of critical thinking development, especially during individual acquisition of knowledge by students of higher educational establishments. Though critical thinking is introduced at school, it shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In addition, the result supports that of Morozova et al’s [ 20 ] study, which showed evidence of the connection between critical thinking ability and independent learning; students who learned to think critically boosted their independent learning. Besides, the current result echoes that of Zuluaga et al [ 37 ], who showed that reading and writing techniques increase students’ argumentation capacity; nonetheless, they lack critical thinking abilities.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, the result supports that of Morozova et al’s [ 20 ] study, which showed evidence of the connection between critical thinking ability and independent learning; students who learned to think critically boosted their independent learning. Besides, the current result echoes that of Zuluaga et al [ 37 ], who showed that reading and writing techniques increase students’ argumentation capacity; nonetheless, they lack critical thinking abilities.…”
Section: Discussionsupporting
confidence: 88%
“…In self-study, learners can construct new knowledge, find new solutions to problems, recognize new challenges to address, and respond to various contexts [ 19 ]. According to [ 20 ], self-study learning enables students to develop a foundation for continued education, allowing them to constantly enhance their abilities and be flexible socially and professionally given the need to identify and justify the practical use of techniques for critical thinking which contributes to the development of independent work of students. In this regard, Morozova et al [ 20 ] showed evidence of the connection between critical thinking ability and independent learning; students who learned to think critically boosted their independent learning.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Proactively ask questions and think critically to solve problems that require alternatives. It allows students to actively participate and develop critical thinking skills, but is also a fun way to learn (Morozova et al, 2022;Siburian et al, 2019). The lecture method makes students passive and does not make them think, so restrictions are needed and educators must provide many opportunities to actively develop their skills (Haftador et al, 2021;Muwahiddah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%